Thermal stability and self-reduction of a new red phosphor NaMg(PO3)3:Mn2+. Issue 16 (28th March 2022) - Zhu, Shuang-Yin; Zhao, Dan; Dai, Shao-Jie; Zhang, Rui-Juan; Shi, Lin-Ying
Abstract : In this paper, a series of red phosphors NaMg(PO3 )3 : x Mn 2+ were synthesized by high temperature reaction in the open atmosphere. Abstract : For Mn-activated phosphors, the luminescent performance is strongly dependent on the oxidation state of Mn. In this paper, a series of red phosphors NaMg(PO3 )3 : x Mn 2+ (NMP: x Mn 2+ ) were synthesized by high temperature solid-state reaction in the open atmosphere. The single oxidation state of Mn 2+ was confirmed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and photoluminescence spectroscopy (PL). We suspected that a self-reduction process occurred to prevent the oxidation of Mn 2+ . The doped Mn 2+ ions occupy the strong crystal field environment of the Mg site (octahedral point), forming a red luminescence center with a peak position centered at 630 nm and a full width at half maximum (FWHM) of 80 nm. The thermal stability and quenching luminescence are explained by the temperature dependence of the PL spectrum. The results show that the NaMg(PO3 )3 :Mn 2+ red phosphor has potential applications in LED backlight display areas.